Use of Rice Husk and Coconut Shell Ash in Concrete Production - Mokhtar, Mardiha; Abdul Halim, Nurul Ain Fakhirah; Mahmod, Nur Hizati; Mohd Rashdan, Nurin Nabila (Multidisciplinary Applied Research and Innovation, 2022)
Rice husk and coconut shell are produced in large quantities that need to be burned in an open air to disposed it. Due to high quantities of silica in the rice husk and high activated carbon in the coconut shell, it will cause some disposal problems in order to dispose it. The objective of this study is to determine the suitable material between rice husk and coconut shell as a partial replacement of material in the production of concrete by comparing the data gathered from previous researchers. Rice husk ash contain around 85% to 90% of amorphous silica that can increase the strength of concrete due to pozzolanic reactions. Coconut shell ash can produce concrete that have good impact resistance and smooth surface on one surface of coconut shell can increase the workability strength of concrete. Data collected from previous researchers and compared the properties of rice husk concrete and coconut shell concrete to determine the suitable material as a partial replacement of material in concrete. The result obtained show that rice husk is suitable as a partial replacement of material in concrete as it does not show significant decrease the strength of concrete compared to coconut shell. The recommendation is the partial replacement of rice husk and coconut shell suitable in the production of lightweight concrete as it can use under low loads and dry applications.